Die Anfänge der europäischen Verfassungsgerichtsbarkeit - Olechowski, Thomas (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2020)
In the field of constitutional jurisdiction, there are two models: the American model, which dates back to the late 18th century, in the early years of the United States. And the European model that is often associated with Hans Kelsen, the ”architect” of the Austrian constitution of 1920. However, the Austrian Constitutional Court is not the first of its kind, the Constitutional Court of Czechoslovakia is a few months older, but it hardly showed any activity. The triumphal march of this model began after 1945 and is a part of most European constitutions today. The article examines the beginnings of this European model and explains its basic principles.